Medios virtuales y su influencia en el reclutamiento de personal en las entidades públicas y privadas de la ciudad de Huamachuco, período 2014 - 2015 - Paredes López, Marcos Noé (2016)
This thesis has been held in the city of Huamachuco in La Libertad, Peru. The overall objective is to "sustain the relationship of influence between Virtual Media and personnel recruitment in public and private entities in the city of Huamachuco. The problem is formulated as follows: To what extent the use of Virtual Media influence the Recruitment of Personnel in Public and Private Entities of the City of Huamachuco, period 2014 - 2015?. In terms of methodology they were applied to a sample survey of five representatives of public and six private, the population being small is equal to the sample. After obtaining the data, we have been processed the results that have allowed qualify the study variables with indicators; then he has performed the analysis of the discussion, which allowed to test the validity of the hypothesis: "The use of Virtual Media, presents differences and influences significantly in the Recruitment of Personnel in Public and Private Entities city Huamachuco, period 2014 - 2015". As the final part they have been formulated conclusions and recommendations. The main conclusion confirms that private companies have higher public entities, both generally and in terms of dimensions and indicators in both study variables scores. The main recommendation states that , due to the high influence of the use of Virtual Media on the effectiveness of staff recruitment , organizations must acquire the necessary (equipment technology : PCs , software : web pages , programs, design processes ; and facilities internet network ) , and also train staff in the use of so-called virtual media.